Practical Application of Methods for Enhancing the Independent Work of Students in Foreign Language - Ibragimov Nuriddin Talibovich (International Journal on Integrated Education, 2022)
The article deals with the issues based on analyzing methods for enhancing the independent work of students in foreign language. It is known that, properly organized and skillfully controlled independent work will encourage students to study and use a foreign language, contribute to the development of their individual cognitive abilities in solving problems, form creative thinking skills and expand professional opportunities, provide a real intercultural context of communication. We consider the development of educational and methodological support for the educational process in the context of expanding the educational autonomy of students and intensifying their self-educational activities in the study of a foreign language as a promising direction for further research of the identified problem.